Did Romanization impact Gallic pig morphology? New insights from molar geometric morphometrics. (May 2015) - Duval, Colin; Lepetz, Sébastien; Horard-Herbin, Marie-Pierre; Cucchi, Thomas
Abstract: In Western Europe, at the turn of our era, the emergence of the Roman economic and agropastoral model is considered as the trigger for morphological changes experienced by livestock. This assumption is now undermined, reviving questions of the origin and mechanism of these changes as well as the influence of Gaul's agricultural particularities in the process. To investigate this question we used a geometric morphometric approach to study the phenotypic relationships of almost 600 dental remains of pigs (Sus scrofa domesticus) from 11 Gallic and Italian sites, and pinpoint evidence of Roman or indigenous signature on the livestock. The comparison of these different samples allowed us to demonstrate that the link between the Roman and Gallic pigs is weak, and, more importantly, that each of the two territories seem to follow its own livestock management model. Furthermore, each region or settlement within Gaul adopted their own particular pastoral or supplying strategies; apart from two urban sites of central Gaul which showed clear phenotypic relationships with southern populations. These results suggest that the pigs' morphology depended mainly on agricultural and economic characteristics of the different territories, within Gaul and Italy, except perhaps on some urban sites with different supply strategies. It seems, therefore, that the changing economic environment impacted both provinces independently, or at least differently, since it cannot be excluded that there may have been some commercial relationships between them. Highlights: Local and regional conservatism of pig phenotypes. No significant environmental influence over the molar size and shape variation of pigs. No clear evidence of Roman influence on Gallic pig morphology. Italian and Gallic pigs differ in size, shape and in the dynamic of their change over time. Pig husbandry changes in Gaul must now be perceived as mainly driven locally.